2022
DOI: 10.1136/archdischild-2022-324530
|View full text |Cite
|
Sign up to set email alerts
|

Can we balance early exogenous surfactant therapy and non-invasive respiratory support to optimise outcomes in extremely preterm infants? A nuanced review of the current literature

Abstract: Therapeutic advances have significantly improved the survival of premature infants. However, a high burden of bronchopulmonary dysplasia (BPD) persists. Aiming at prevention of neonatal lung injury, continuous positive airway pressure (CPAP) and non-invasive ventilation (NIV) strategies have replaced mechanical ventilation for early respiratory support and treatment of respiratory distress syndrome. Multiple randomised controlled trials have demonstrated that broad application of CPAP/NIV decreases exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…22 One may argue that FiO 2 and respiratory effort on clinical exam should be able to predict surfactant need; however, a study has shown that FiO 2 remains a poor predictor for surfactant deficiency. 4 LUS offers additional advantages in predicting surfactant need and is supported by the European consensus guidelines on the management of RDS. 3,8 Quality improvement projects have shown that using LUS can improve the timeliness of surfactant administration and reduce unnecessary oxygen exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 One may argue that FiO 2 and respiratory effort on clinical exam should be able to predict surfactant need; however, a study has shown that FiO 2 remains a poor predictor for surfactant deficiency. 4 LUS offers additional advantages in predicting surfactant need and is supported by the European consensus guidelines on the management of RDS. 3,8 Quality improvement projects have shown that using LUS can improve the timeliness of surfactant administration and reduce unnecessary oxygen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, around 50% of preterm neonates fail on nCPAP alone and need surfactant therapy. 4 Timely and accurately differentiating the preterm neonates who will benefit from surfactant administration remains challenging. The European consensus guidelines recommend surfactant administration threshold as >30% supplemental oxygen for preterm neonates on continuous positive airway pressure 6 cm H 2 O.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dual strategy, early noninvasive respiratory support with early surfactant administration may increase NIV success. 4,5 The ideal time for surfactant administration has been debated. 6 Current guidelines for RDS management suggest early rescue surfactant administration.…”
mentioning
confidence: 99%
“…Dual strategy, early noninvasive respiratory support with early surfactant administration may increase NIV success. 4 5…”
mentioning
confidence: 99%